THE ROLE OF MUNAVVAR KORI ABDURASHIDKHANOV IN THE EMERGENCE OF THE NATIONAL JADID MOVEMENT (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article examines the Jadid movement in the country and the history of its emergence. The book also briefly discusses the unrivaled contribution of Munavvarkori Abdurashidkhanov, one of the great enlightened Jadids, to the Jadid movement and his life.